Spotlight on data : the power of deep learning in the hands of domain experts (O'Reilly Media, 2019)
"In this Spotlight on Data, find out how Silicon Valley Innovation Laboratories, a research center established by Japanese electric and electronics equipment company Furukawa Electric, trained a deep learning model to recognize manufacturing defects in fiber optic cables using platform.ai, without writing any code or needing the help of a data scientist."--Resource description page